STRATEGI BERTAHAN HIDUP KARYAWAN SETELAH PENUTUPAN PABRIK KARET PT.BANGKINANG DI KELURAHAN LANGGINI KOTA BANGKINANG - Sri Wahyuni Damanik; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Rubber factories are a very strategic role as the foundation of foreign exchange. With the end of PT. Rubber factory operations this program will affect changes in the socio-economic conditions of its employess. The purpose of this study was to find out how the employee survival strategy after the closure of the PT. Bangkinang, Langgini Village, Bangkinang City. This study uses a qualitative approach with descriptive analysis. The selection of informants in this study was carried out by purposive sampling technique that is taking data from informants based on certain criteria. Thesa criteria are employees  who have worked at PT. Rubber factories Bangkinang. Data collection techniques used in this study were interviews, observation, documentation. The results of this study state that the socio-economic conditions of former employees after the closer of PT. Bangkinang has experienced a decline as well as low income, making ex-employees a strategy to survive. This strategy is to find work and look for loans. Social capital plays a role in the survival strategy of former employees. The strategy to find a loan can be done by employees because of the willingness tohelp from tha party who gives the loan. This is because of the existance of beliefs and norms that shape the attitude of mutual assistance.  Similarly, the strategy of looking for work is done by former employees because it is suported by social networks. Social networks produce good cooperation, helpeach other, a sense of brotherhood an kinship.  Keywords: Survival Strategy, Socio-Economic Conditions, Rubber Factory.